A Novel Gene Expression Scoring System Predicts Recurrence in Non‐Muscle‐Invasive Bladder Cancer Patients - Emina Kayama; Motohide Uemura; Akifumi Onagi; Satoru Meguro; Soichiro Ogawa; Kei Yaginuma; Kanako Matsuoka; Seiji Hoshi; Tomoyuki Koguchi; Junya Hata; Yuichi Sato; Hidenori Akaihata; et al. (Cancer Medicine)
ABSTRACT Background Despite the high recurrence rate of non‐muscle‐invasive bladder cancer (NMIBC), there are limitations in accurately predicting recurrence after transurethral resection of bladder tumor (TURBT) based on clinicopathological factors alone. However, prediction of recurrence using biomolecular characteristics of bladder tumors has not been applied to clinical practice. The objective of this study was to establish a new gene expression scoring system for identifying patients at high risk of recurrence. Methods NMIBC and normal bladder samples were subjected to microarray analysis to obtain gene expression profiles. We identified 6 genes that were specifically upregulated in bladder cancer and also in recurrent cases. All patients were randomly grouped into a discovery cohort (n = 59) and a validation cohort (n = 30). Gene expression score (GES) was defined as the mean Z‐score of the 6 genes specific for recurrent bladder cancer. Results The intravesical recurrence rate of the high GES group (n = 38) was higher than the low GES group (n = 21). GES was significantly associated with recurrence‐free survival in the validation cohort as well. In prognostic analysis, the European Organization for Research and Treatment of Cancer (EORTC) risk classification was not related to recurrence after TURBT in either univariate or multivariate analysis. On the other hand, the GES we developed was an independent factor for recurrence in NMIBC. Conclusions A novel gene expression scoring system was shown to predict recurrence in NMIBC patients after TURBT and might be helpful in clinical decision‐making for NMIBC patients.